(untitled) (Sociologisk Forskning, 1993)
From ideal via paradox to problem. Individuality and love in Niklas Luhmann’s systems theory This paper deals, on the one hand, with the question of man as an individual and his relationship to society and, on the other hand, with the sociology of love and intimacy and hence with the sociology of modern individualization. The aim is to introduce for Scandinavian sociology the German sociologist Niklas Luhmann, especially with regard to these themes and, at the same time, his radical and new conception of social systems. It is often suggested that sociological systems theory can only deal with macro level problems, and not with the micro level; of understanding problems on the individual level. In Luhmann’s approach this is no longer the case. The individual is conceived of as strictly belonging outside of society, as part of the environment. Only as person is it possible to identify man inside social systems. But in using the distinction between system and environment, both environment and system is focused upon. Love is analyzed primarily as a semantic code and not as a feeling (as is often the case). The thesis is that only as a code can love be expressed in its emotionality. In his book Love as Passion (an excellent example of historical sociology) the code of love is observed from Middle Ages as an ideal form, via its form of paradox, till today when love as a problem of the family system is penetrated by specialists of all kinds. Luhmann’s intention is not to find a solution for the family, but to provide an understanding for solutions which are contingent.